A Characterization of the Electrophysiological and Morphological Properties of Vasoactive Intestinal Peptide (VIP) Interneurons in the Medial Entorhinal Cortex (MEC) - Badrinarayanan, Saishree; Manseau, Frédéric; Williams, Sylvain; Brandon, Mark P. (Frontiers in Neural Circuits, 2021)
Circuit interactions within the medial entorhinal cortex (MEC) translate movement into a coherent code for spatial location. Entorhinal principal cells are subject to strong lateral inhibition, suggesting that a disinhibitory mechanism may drive their activation. Cortical Vasoactive Intestinal Peptide (VIP) expressing inhibitory neurons predominantly contact interneurons, providing a local disinhibitory mechanism, yet little is known about this cell type in the MEC. To investigate the electrophysiological and morphological properties of VIP cells in the MEC, we use in vitro whole-cell patch clamp recordings in VIPtdTom cre mice. We report several gradients in electrophysiological properties of VIP cells that differ across lamina and along the dorsal-ventral MEC axis. We additionally show that VIP cells have distinct morphological features across lamina. Together, these results characterize the cellular and morphological properties of VIP cells in the MEC.